The Dry Season in Haiti: a Window of Opportunity to Eliminate Cholera - Rebaudet, Stanislas (Public Library of Science, 2013)
Background: Since the beginning of the cholera epidemic in Haiti, attack rates have varied drastically with alternating peak and lull phases, which were partly associated with the fluctuating dry, rainy and cyclonic seasons. According to a study conducted in 2012, the toxigenic V. cholerae O1 strain responsible for the outbreak did not settle at a significant level in the Haitian aquatic environment. Therefore, we hypothesize that some areas of lingering cholera transmission during the dry season could play an important role in the re-emergence of outbreaks during the rainy season. Our objective was therefore to describe the dynamics of cholera and assess the fight against the disease during the dry season. Methods: A field study was conducted from February 19 to March 29, 2013. After identifying the affected communes by analyzing the national cholera database, we visited corresponding health facilities to identify patient origins. We then conducted a field assessment of these foci to confirm the presence of cholera, assess factors associated with transmission and examine the activities implemented to control the epidemic since the beginning of the current dry season. Results: We found that the great majority of Haitian communes (109/140) presented no sign of cholera transmission in February and March 2013. Suspected cases were concentrated in a small number of urban and rural areas, almost all of which were located in the northern half of the country and often in inland locales. In these areas, community health activities appeared insufficient and were often inappropriately targeted. Out of 49 analyzed foci, only 10 had benefited from at least one intervention involving the distribution of water treatment products together with an awareness campaign since December 2012. Conclusion: Cholera continues to affect Haiti as observed in early 2013; however, activities implemented to interrupt cholera transmission appear insufficient and poorly suited. This deficiency in the fight against cholera, especially at a period when transmission is weak, may explain the persistence of cholera even in the absence of significant aquatic reservoirs in Haiti.